PENGARUH DESENTRALISASI FISKAL TERHADAP PERTUMBUHAN EKONOMI DAERAH DAN KETIMPANGAN PENDAPATAN (STUDI KASUS : KABUPATEN/KOTA DI JAWA TENGAH) - Lintantia Fajar Apriesa; Miyasto Miyasto (Universitas Diponegoro, 2013)
The implementation of regional autonomy in the District / City of Central Java is still not implemented optimally. Regional autonomy has the primary purpose of public services closer to the community. Development in Central Java region including behind because many areas - areas in Java, which has a low level of GDP. The state of the education sector, the transportation sector, unemployment and poverty in the province of Central Java is a reflection of the real against the public policy of regional autonomy, and achievement of development results in the development process in Central Java depends on the management policy of the Government. Theory of Kuznets about curve inverted U-shaped this suggests that there are stages through which the growth process when the initial revenue growth has not been evenly distributed levels of income inequality, but at this stage - the next step will equitable income distribution and inequality is likely to be small. Kuznets argued the stages - stages in the development process areas for the presence of income inequality. The results in this research, using Recursive Models as well as the methods used PLS (Panel Least Square) method fixed Cross-sections, that economic growth there is a positive and significant impact on fiscal decentralization and fiscal decentralization also a positive and significant the inequality region.